Конечноэлементный анализ резонансных режимов топливоподающего тракта ракеты - Филипковский, С. В.; Аврамов, К. В. (НТУ "ХПИ", 2009)
Запропоновано метод аналізу частот і форм поздовжніх коливань рідини в магістралі окислювача рідинного ракетного двигуна. Розроблено скінчений елемент, що враховує стискальність рідини й пружність стінок труби. Запропонований скінчений елемент, який апроксимує гідроамортизатор, що знижує власні частоти.

The method of a liquid longitudinal oscillations modal analysis in an oxidizer line of the fluid-propellant rocket engine is offered. The finite element which is taking into account a liquid compressibility and the pipe walls elasticity is developed. The finite element which approximates the hydroshock reducer that decreases the natural frequencies is offered.
Keywords: топливные магистрали; резонансные частоты колебаний; метод конечных элементов; газожидкостный демпфер; окислители